The acute effects of dual task on the motor and cognitive performances in taekwondo players - Simsek, D.; Yildiz, A. B. (Kinesiologia Slovenica, 2022)
Dual-task paradigms are typically used for two different aims. The first aim is to investigate the demands of attention of a motor task, and the other aim is to examine the effects of simultaneous cognitive or motor tasks on motor performance. The purpose of the current research is to determine the changes in motor performance times of national (experts) and non-national players (novices) during motor tasks including cognitive cues. Fifteen male national taekwondo players, who are active in taekwondo (age=17.8±1.65 years; training experience=6-13 years; training frequency=5-6 day\\week, 2-3 hour\\day) and 15 male non-national taekwondo players (age=16.8±1.68 year; training years=3-9 years; training frequency=1.86 ± 0.22 hour\\day and 4.33 ± 0.61 day / week) were voluntarily included in the study. FitLight Trainer™ system was used to determine the dual-task performance of participants. The performance time of expert players was statistically and significantly lower compared to novice players (Random Test: t=3.884, p <0.05; Cue Test: t=3.155, p <0.05; Mixed Cue Test: t=3.013, p<0.05). This study reveals; (1) expert players automatically make postural control adjustments during the motor task, and they put less cognitive effort than they are minimally considered, (2) they show a positive development in regular physical activities and training, and other systems, especially in the proprioceptive system, involved in balance control. We conclude that performances of novices suffer considerably in motor-cognitive dual-task situations. Therefore, training with dual-tasks might be useful working memory skills and attentional control of novice players. We conclude that dual-tasks acutely impacts motor and cognitive performance. Therefore, training with dual-tasks might be useful working memory skills and attentional control of novice players. We conclude that dual-tasks acutely impacts motor and cognitive performance. In future studies, dual-task paradigms between different combat sports and comparisons of postural control strategies should be measured.